Role of Type I Interferon (IFN) in the Respiratory Syncytial Virus (RSV) Immune Response and Disease Severity - Hijano, Diego R.; Vu, Luan D.; Kauvar, Lawrence M.; Tripp, Ralph A.; Polack, Fernando P.; Cormier, Stephania A. (Frontiers in Immunology, 2019)
Respiratory syncytial virus (RSV) is the most common cause of lower respiratory tract disease in children from 1-3 years of age. Increased morbidity and mortality have been reported in high-risk patients, such as premature infants, patients with cardiac disease, and severely immune compromised patients. Severe disease is associated with the virulence of the virus as well as host factors specifically including the innate immune response. The role of type I interferons (IFNs) in the response to RSV infection is important in regulating the rate of virus clearance and in directing the character of the immune response, which is normally associated with protection and less severe disease. Two RSV nonstructural proteins, NS1 and NS2, as well as the envelope G glycoprotein are known to suppress type I IFN production and a robust type I IFN response to RSV does not occur in human infants or neonatal mouse models of RSV infection. Additionally, presence of type I IFNs are associated with mild symptoms in infants and administration of IFN-α prior to infection of neonatal mice with RSV reduces immunopathology. This evidence has driven RSV prophylaxis and therapeutic efforts to consider strategies for enhancing type I IFN production.